A systematic review of treatments for pityriasis lichenoides. (8th August 2019) - Bellinato, F.; Maurelli, M.; Gisondi, P.; Girolomoni, G.
Abstract: Pityriasis lichenoides (PL) represents a spectrum of inflammatory skin diseases comprising pityriasis lichenoides et varioliformis acuta (PLEVA) and pityriasis lichenoides chronica (PLC). This study aimed to provide a summary of effective treatments for PL. A systematic review was performed according to PRISMA guidelines for studies investigating PL treatment including ≥3 subjects and published in English between 1 January 1970 and 15 April 2019. A total of 441 papers were screened, and 37 original manuscripts meeting the inclusion and exclusion criteria were found, including 12 case series, 18 reviews, four prospective studies, two comparative studies and a single randomized controlled study. In most studies, ultraviolet (UV) phototherapy (narrow‐band UVB, broadband UVB, UVA1 or PUVA) was used. Clearance rates with the different modalities are hardly comparable between different studies, ranging approximately between 70% and 100%. Narrow‐band UVB showed an efficacy similar to PUVA as such as the combination of UVA and UVB vs. PUVA. Oral erythromycin showed clearance rates ranging between 66% and 83%, whereas methotrexate up to 100% but in small and dated studies. Evidence for other treatments is scarce. There is a lack of high level of evidence studies on PL treatment. The interpretation of the results is biased by the possible auto‐resolution of the disease, the sample heterogeneity between children and adults and the short follow‐up period of the studies. Only some studies investigated how results were durable after cessation of therapy. Quality of life and the impact of treatment were never assessed. According to the results of this review, we suggest narrow‐band UVB phototherapy as first‐line treatment. Oral erythromycin with or without topical corticosteroids and low‐dose methotrexate as second‐line therapies. High‐powered studies and randomized controlled trials are needed to establish the optimal treatment for PL.